Role of family structure and parenting style in adolescent pregnancy in Surabaya, Indonesia - Anifah, Fulatul; Dasuki, Djaswadi; K, Herlin Fitriana; Triratnawati, Atik (Majalah Obstetri & Ginekologi, 2018)
Objectives: This study aimed to examine the relationship between family structure and parenting style and their association with adolescent pregnancy in Surabaya. Materials and Methods: A mixed-methods approach was employed, combining a case–control design with a case study. Data were collected through questionnaires and in-depth interviews. The study included 46 adolescents (23 cases and 23 controls) selected using purposive sampling, along with six adolescents as key qualitative participants. Quantitative data were analyzed using univariate, bivariate (Chi-square), and multivariate (multiple logistic regression) analyses with a significance level of p = 0.05 and a 95% confidence interval (CI). Qualitative data were analyzed thematically based on in-depth interviews. Results: Family structure was not statistically significant (OR = 10.53; 95% CI = 0.657–168.93), though it showed social relevance. Parenting style was also not significantly associated with adolescent pregnancy (OR = 1.191; 95% CI = 0.373–3.806). However, respondent education was significantly associated with adolescent pregnancy (OR = 559.76; 95% CI = 3.608–23,026.4). No significant associations were found for parental education, employment status, or residential setting. Parenting style appeared to be influenced by the quality of communication between parents and adolescents. Conclusions: Low educational attainment was identified as a major risk factor for adolescent pregnancy. Additionally, adolescents from extended families or single-parent households appeared more likely to experience teenage pregnancy.